THE MELT ROCKS OF THE BOLTYSH IMPACT CRATER, UKRAINE, USSR - Gurov E.P.; Grieve R.A.F.; Reny G.; Ryabenko V.A. (My University, 1987)
The 10012 m.y., 25 km diameter Boltysh impact crater was formed in Precambrian granites and granite gneisses of the Ukrainian Shield. The crater deposits have undergone minimal post-impact erosion and it is possible to study a complete vertical section of the underlying 200 m thick melt sheet. The melt rocks, as sampled in two drill holes, can be subdivided into two major textural classes: microcrystalline and glassy. The microcrystalline melt rocks form an uppermost and two lowermost units, with the glassy variety occupying the middle of the melt sheet. The microcrystalline units contain 25% zoned plagioclase phenocrysts set in a microcrystalline matrix of intergrown alkali feldspar and quartz. Pyroxene has been replaced by sheet-silicates. Mineral and lithic clasts make up 5–15% and show varying degrees of shock and resorption. The glassy melt rocks are characterized by 10–30% zoned plagioclase and 5–10% orthopyroxene set in a fresh to partially devitrified glassy matrix. Clast content is 2O3/FeO ratio and the alkalis between the microcrystalline and glassy varieties. The increase in matrix crystallinity at the upper and lower contacts is contrary to observations at other impact melt sheets, where greater matrix crystallinity occurs in the interiors of the melt sheets. One possible explanation is that the melt matrix was originally glassy throughout, due to its high SiO2 content, and the microcrystalline matrix is the result of extensive devitrification involving minor alkali exchange with circulating ground-waters.
Keywords: Precambrian; Precambrian; Докембрий